Neurosarcoidosis: unusual presentations and considerations for diagnosis and management. Issue 1101 (5th December 2016) - Radwan, Walid; Lucke-Wold, Brandon; Robadi, Ibrahim Ahmed; Gyure, Kymberly; Roberts, Thomas; Bhatia, Sanjay
ABSTRACT: Background: Sarcoidosis is a chronic, multisystem disease characterised by non-necrotising granulomatous inflammation of unknown aetiology. Most commonly, the lungs, lymph nodes, skin and eyes are affected in sarcoidosis; however, nervous system involvement occurs in approximately 5%–15% of cases. Any part of the nervous system can be affected by sarcoidosis. Cases: Herein we describe three unusual patient presentations of neurosarcoidosis, one with optic neuritis, a second with hydrocephalus and a third with cervical myelopathy. Conclusions: We include pertinent details about their presentations, imaging findings, pathology, management and clinical course.